2006
DOI: 10.1016/j.bbalip.2006.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Farnesyl phosphates are endogenous ligands of lysophosphatidic acid receptors: Inhibition of LPA GPCR and activation of PPARs

Abstract: Oligoprenyl phosphates are key metabolic intermediates for the biosynthesis of steroids, the side chain of ubiquinones, and dolichols and the posttranslational isoprenylation of proteins. Farnesyl phosphates are isoprenoid phosphates that resemble polyunsaturated fatty alcohol phosphates, which we have recently shown to be the minimal pharmacophores of lysophosphatidic acid (LPA) receptors. Here we examine whether farnesyl phosphates can interact with the cell surface and nuclear receptors for LPA. Both farnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…FPP acts on other membrane receptors: it activates GPR92 and inhibits LPA2 and LPA3 receptors (26,32). In the present study, another activating ligand for GPR92, NAG failed to elevate intracellular Ca 2ϩ level in the keratinocyte experiments.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…FPP acts on other membrane receptors: it activates GPR92 and inhibits LPA2 and LPA3 receptors (26,32). In the present study, another activating ligand for GPR92, NAG failed to elevate intracellular Ca 2ϩ level in the keratinocyte experiments.…”
Section: Discussionmentioning
confidence: 53%
“…RR and the shRNA also prevented FPP-evoked pain behavior, supporting this notion. As well, it is not possible that LPA2 or LPA3 receptor is involved because FPP leads to the opposite result through the receptor inhibition (FPP blocked the LPAinduced intracellular Ca 2ϩ increase in the observations of Liliom et al (32)) Differential roles of FPP may be expected in the different receptor expressers.…”
Section: Discussionmentioning
confidence: 96%
“…The docking simulations also predicted NAG to be a weak activator of the LPA 5 based on weak interactions with the mutated residues Arg-2.60, Arg-6.62, Arg-7.32, and His-4.64 within the binding pocket of our model (Table 2). Based on these predictions, we examined the activation of LPA 5 by NAG, FPP, and FMP, which we had earlier identified as endogenous antagonists of EDG LPA receptors (42). Among this subset of ligands, LPA 18:1 was the most potent in mobilizing Ca 2ϩ in RH7777 cells transiently transfected with LPA 5 (Fig.…”
Section: Selection Of Mutationmentioning
confidence: 99%
“…A separate study with 3T3-L1 cells also showed that 50 mmol/L farnesol, a level comparable to those used in the present study, activated PPARg in a reporter assay; farnesol had the highest potency among several isoprenoids evaluated therein in activating PPARg-regulated FABP4 expression. 6 Farnesyl phosphate and FPP competed with rosiglitazone for PPARg binding with IC50 values for ligand displacement approximating 19 mmol/L, a value much lower than that of farnesol; the latter was nevertheless more efficacious in activating PPARg in CV-1 cells transfected with a reporter gene, 19 suggesting a possible farnesol metabolite with higher potency than those of the phosphorylated products of farnesol. In human HCT, 116 colorectal cancer cells, farnesol at 50 and 100 mmol/L increased PPARg promoter activity, an effect that mediates the growth-inhibitory activity of farnesol.…”
Section: Discussionmentioning
confidence: 99%